2020
DOI: 10.3389/fpsyt.2020.00480
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Appetite-Regulating Hormones Provides Further Evidence of Altered Adipoinsular Axis in Early Psychosis

Abstract: risk of psychosis are needed to provide insights into causal mechanisms underlying our results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…The association between leptin and negative symptoms is in keeping with a meta-analysis of patients with schizophrenia (Stubbs et al, 2016), although this was not observed in smaller studies of first episode of psychosis (FEP) patients (Chouinard et al, 2019; Lis et al, 2020). However, in FEP cases Lis et al, (2020) observed a correlation between leptin and cognitive dysfunction, a domain of psychopathology somewhat linked to negative symptoms. Recently, a Mendelian randomisation (MR) study did not find an association between leptin and schizophrenia (Perry et al, 2021a), bringing into question whether leptin plays a causal role in the illness.…”
Section: Discussionsupporting
confidence: 68%
“…The association between leptin and negative symptoms is in keeping with a meta-analysis of patients with schizophrenia (Stubbs et al, 2016), although this was not observed in smaller studies of first episode of psychosis (FEP) patients (Chouinard et al, 2019; Lis et al, 2020). However, in FEP cases Lis et al, (2020) observed a correlation between leptin and cognitive dysfunction, a domain of psychopathology somewhat linked to negative symptoms. Recently, a Mendelian randomisation (MR) study did not find an association between leptin and schizophrenia (Perry et al, 2021a), bringing into question whether leptin plays a causal role in the illness.…”
Section: Discussionsupporting
confidence: 68%
“…We observed an association between leptin and negative, but not positive, psychotic symptoms. The general finding of an association between leptin and psychotic disorder is in keeping with a meta-analysis of patients with schizophrenia (Stubbs et al, 2016), although this was not observed in smaller studies of first episode of psychosis (FEP) patients (Chouinard et al, 2019;Lis et al, 2020). Similarly, a Mendelian randomisation (MR) study did not find an association between leptin and schizophrenia (Perry et al, 2021a), bringing into question whether leptin plays a causal role in the illness.…”
Section: Comparison With Previous Findings: Psychosismentioning
confidence: 56%
“…In schizophrenia, while previous studies have measured plasma leptin in patients with FEP, findings are very conflicting. For instance, a recent meta-analysis and clinical studies found that plasma leptin production was significantly reduced in antipsychotic-naïve FEP patients compared to the CNT subjects[ 69 - 71 ], whereas other studies found opposite results[ 72 - 74 ]. The reasons for these discrepancies are not clear; however, a number of factors including gender, sex hormones, age, eating behavior, duration of illness, smoking, and other medications may affect leptin production.…”
Section: Discussionmentioning
confidence: 99%